Sistem Pendukung Keputusan Pemilihan Guru Teladan SD Negeri Ceger 02 Pagi Menggunakan Metode Analitical Hierarcy Proces - Oka Mahendra; Kresna Ramanda (LPPM STIKI MALANG, 2020)
The selection of exemplary teachers is done every semester, which is done six months to determine who deserves to be an exemplary teacher. In this case the teacher's assessment is exemplary by the teachers and leaders. schools do not have methods that can deal with priority issues with work ethic criteria, objectives, scholarship, inclusive attitudes, communication is the benchmark in selecting model teachers. In addition, schools also often have difficulty in selecting exemplary teachers to be assessed. this becomes a flaw to determine whether or not the teacher is selected as an exemplary teacher. Therefore it is necessary to test the results of these methods to see the strength of the relationship of the results obtained with the ranking of decisions made. the stronger the relationship will certainly be better. This can be seen from the calculation of the Analytical Hierarchy Process (AHP), which is the Hierarchy Consistency Ratio (CRH) in the selection of model teachers in Ceger State Elementary School 02 in the morning of East Jakarta, obtained a value> 0.1 which is = 0.02553225 which means the calculation results can be declared correct .